2010
DOI: 10.1111/j.1528-1167.2009.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of smoking, caffeine, and alcohol as risk factors for seizures or epilepsy in young adult women: Data from the Nurses’ Health Study II

Abstract: SUMMARY Purpose Seizures and epilepsy are associated with significant disability and substantial treatment costs, yet little is known about primary prevention. We prospectively examined the association of cigarette smoking, caffeine use, and alcohol intake with risk of seizure or epilepsy among women, aged 25-42 years, in the Nurses’ Health Study II. Methods Participants provided dietary and cigarette smoking information on multiple questionnaires beginning in 1989. Among 116,363 women at-risk for incident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 36 publications
2
54
1
1
Order By: Relevance
“…For example, long-term moderate alcohol intake was not associated with seizure or epilepsy. 38 We also found that moderate alcohol consumption had no substantial adverse effect on renal function in women over an 11-year follow-up period. 39 In a cross-sectional study of alcoholic intake and early lens changes, alcohol consumption, especially liquor and wine, was positively related to nuclear opacity, and wine consumption was associated with a lower odds of cortical opacity.…”
Section: Other Notable Health Conditions and Diseasesmentioning
confidence: 66%
“…For example, long-term moderate alcohol intake was not associated with seizure or epilepsy. 38 We also found that moderate alcohol consumption had no substantial adverse effect on renal function in women over an 11-year follow-up period. 39 In a cross-sectional study of alcoholic intake and early lens changes, alcohol consumption, especially liquor and wine, was positively related to nuclear opacity, and wine consumption was associated with a lower odds of cortical opacity.…”
Section: Other Notable Health Conditions and Diseasesmentioning
confidence: 66%
“…A similar effect of tobacco use has only been described in autosomal dominant nocturnal frontal lobe epilepsy . Contrary to our findings, current smoking was associated with a 2.6‐fold risk for seizure occurrence in 25–42‐year‐old female nurses . However, the inverse association found in our study may reflect a withdrawal effect of chronic nicotine stimulation during treatment of acute ischaemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…To identify incident cases, we mailed participants who self‐reported new seizure/epilepsy diagnoses after 1989 a validated seizure supplementary questionnaire (Dworetzky et al., 2009) and requested permission to access medical records. The questionnaire assessed detailed information regarding the age at first seizure, the number of lifetime seizures, family history, medication history, etiology provided by physician, seizure description (i.e., limb jerks, warnings, alteration in awareness), and diagnostic procedures [magnetic resonance imaging (MRI), computed tomography (CT), electroencephalography (EEG), video‐EEG, and neurologic consultation].…”
Section: Methodsmentioning
confidence: 99%